Factors Affecting Green Practices Adoption in Maize Stalks, Cobs, and Peels Disposal: A Case Study of Chiang Rai Maize Farmers - Ho, Phutawan; Thepchalerm, Teeris (International Journal of Multidisciplinary in Management and Tourism, 2021)
Although maize cultivation has been considered one of the essential crops of Thailand’s agricultural and livestock industry, it should not overlook the negative impact on people’s environmental aspects and health caused by traditional maize residues disposal. This research aims to identify the factors affecting green practices adoption in maize stalk, cobs, and peels disposal. The population group of this study is the maize farmers who cultivated in Chiang Rai province. The sample of this research is the maize farmers from Theong and Chiang Khong districts. Using an interviewer-administered questionnaire, the researchers used a convenient sampling method and collected data from 410 maize farmers. The researchers used Binary Logistic Regression to analyze the factors affecting green practices adoption because the value of the dependent variable is dichotomous. With a confidence level of 95 percent, the results reveal that selling price is the most crucial factor followed by farmers’ knowledge, geographical condition, and government measures, respectively. Researchers suggest that the government should utilize its policies to generate more efficient and effective outcomes by educating the farmers and facilitating the green practices adoption processes. Lastly, there should be proper and continuous projects and monitoring measures for future improvements.